HUBUNGAN PENDIDIKAN KARAKTER DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR PKN KELAS IV SDN SEGUGUS DOKTER WAHIDIN SUDIRO HUSODO METRO BARAT LAMPUNG - Nuraini, Siti; Pangestu, Deviyanti; Kembar Habibi, Roy (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2024)
The problem in this study was the low grade IV elementary school yield of Civics learning outcomes of the Wahidin SudiroHusodo Metro Barat group of doctors. This study aims to determine the positive and significant relationship between character education and learning motivation with learning outcomes.This type of research is ex-postfacto correlation.The population is 94 educators and the entire population is used as the research sample. The instrument for data collection is a questionnaire with a Likert scale, which was previously tested for validity and reliability. Data analysis using product moment correlation and multiple correlation. The results showed that there is a positive and significant relationship between character education and learning motivation with learning outcomes. indicated by a correlation coefficient of 0.776 at the level of "strong". Character education and learning motivation greatly impact Pkn learning outcomes. Character education can shape the character of students to become moral individuals. High learning motivation will have an impact on the learning outcomes to be obtained.